2022
DOI: 10.1021/jacs.2c05358
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis-Inspired, Divergent Synthesis of Spirochensilide A, Spirochensilide B, and Abifarine B Employing a Radical-Polar Crossover Rearrangement Strategy

Abstract: Triterpenoids and related abeo-steroids are of interest to the scientific community for their potent and varied biological activities as well as their unique structures. Within this large and diverse family of natural products, the fir metabolites (−)-spirochensilide A and B are particularly noteworthy for their controversial biogenesis. We herein report the chemical synthesis of the spirochensilides, which involves a concerted sequence of bioinspired rearrangements contributing to its resolution. Points of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…The spectra and physical properties of 1 were identical to those reported for naturally occurring spirochensilide A. While we were preparing this communication, Heretsch et al reported their elegant syntheses of abifarine B and spirochensilides A and B by means of a bioinspired strategy . The key steps of our synthesis are bioinspired (Wagner–Meerwein rearrangement followed by Meinwald rearrangement), and both of our syntheses are modifications of the proposed biosynthetic pathway.…”
supporting
confidence: 68%
See 3 more Smart Citations
“…The spectra and physical properties of 1 were identical to those reported for naturally occurring spirochensilide A. While we were preparing this communication, Heretsch et al reported their elegant syntheses of abifarine B and spirochensilides A and B by means of a bioinspired strategy . The key steps of our synthesis are bioinspired (Wagner–Meerwein rearrangement followed by Meinwald rearrangement), and both of our syntheses are modifications of the proposed biosynthetic pathway.…”
supporting
confidence: 68%
“…This analysis revealed that in some lanostanes, such as abiesatrine A ( 2 ) and neoabiestrine F ( 3 ), the C18 methyl group has migrated from C13 to C17 and the C8–C9 double bond is not oxidized . This suggests that during spirochensilide A biosynthesis, the Wagner–Meerwein-type methyl migration may occur before the Meinwald rearrangement, which was also concluded in Heretsch’s search for natural products that are potentially biogenetically related to the spirochensilides . Although various types of Meinwald rearrangements have been explored in recent decades, controlling the regio- and stereoselectivity of Meinwald rearrangements of tetrasubstituted epoxides without an adjacent directing group remains challenging, as demonstrated by the work on biomimetic transformations by Gao’s group .…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…For example, in the synthesis of jungermannenone C ( 92 ) by the group of Lei and Li (Scheme 12), 29 the authors utilized a photochemical 1,3-acyl migration to rearrange the [3.2.1]octene ring system of the ent -kaurane skeleton ( 93 ) into the jungermannenone skeleton, highlighting the unconventional radical mechanism ( I or II ) in revealing exciting new chemistry in the synthesis of terpenoids. Most recently, the group of Heretsch reported the total synthesis of abifarine B ( 94 ), 30 in which a radical-polar crossover approach was developed. The alkoxy radical III , generated by the oxidation of alcohol 95 , underwent 1,5-hydrogen atom transfer (HAT) and oxidation to afford the reactive cationic species V , which triggered the Wagner–Meerwein methanide shift to furnish 96 .…”
Section: Discussionmentioning
confidence: 99%